PERIODONTAL DISEASE AS AN ETIOLOGY OF OROFACIAL AND MUSCOSKELETAL PAINS IN WOMEN (CASE REPORT) - Haryono Utomo; Chiquita Prahasanti (Faculty of Dentistry, Universitas Indonesia, 2015)
Orofacial pain includes pain associated with the hard and soft tissues of the head, face, neck, and all of the intraoral structures. Upon painful episodes, consuming analgesics, or traditional medicine are relatively common. It is also a common sense that high cholesterol and hypertension may contribute to the pain. Since most pain sufferers are women, estrogen is proposed to be a modulator of pain perception. Nevertheless, the mechanism of pain modulation in women is still in controversy. Systemic manifestations of periodontal disease are widely accepted. However, the role of periodontal disease as an etiology of orofacial and musculoskeletal pain is rarely discussed. Recent study in medical psychoneuroimmunology may reveal the possibility of periodontal disease as an etiology of these painful symptoms. The objective of this study is to reveal the possibility of periodontal disease as an etiology of orofacial and musculoskeletal pain, resulting in the disappearing of the symptoms. Regarding to the amazing results, the conclusion is that especially in women, periodontal disease cause orofacial and muscoskeletal pain especially in women.